2022
DOI: 10.1002/chem.202200300
|View full text |Cite
|
Sign up to set email alerts
|

Cation‐π Interactions between a Noble Metal and a Polyfunctional Aromatic Ligand: Ag+(benzylamine)

Abstract: The structure of an isolated Ag+(benzylamine) complex is investigated by infrared multiple photon dissociation (IRMPD) spectroscopy complemented with quantum chemical calculations of candidate geometries and their vibrational spectra, aiming to ascertain the role of competing cation‐N and cation‐π interactions potentially offered by the polyfunctional ligand. The IRMPD spectrum has been recorded in the 800–1800 cm−1 fingerprint range using the IR free electron laser beamline coupled with an FT‐ICR mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…It can be observed that most of the coordination centers were heavy metals leading to the limitation of their application. [36][37][38] Since 2014, Ca 2+ was used as the coordination center to prepare calcium phenolate complexes with guaiacol and its derivatives as ligands. 39 The essence of this method was to use calcium hydroxide solution to react with guaiacol or its derivatives to produce a coordination compound with a molar ratio of calcium to guaiacol of 1:4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that most of the coordination centers were heavy metals leading to the limitation of their application. [36][37][38] Since 2014, Ca 2+ was used as the coordination center to prepare calcium phenolate complexes with guaiacol and its derivatives as ligands. 39 The essence of this method was to use calcium hydroxide solution to react with guaiacol or its derivatives to produce a coordination compound with a molar ratio of calcium to guaiacol of 1:4.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction system has been extensively used in organic synthesis, 33 food industry 34 and health research, 35 etc . It can be observed that most of the coordination centers were heavy metals leading to the limitation of their application 36‐38 . Since 2014, Ca 2+ was used as the coordination center to prepare calcium phenolate complexes with guaiacol and its derivatives as ligands 39 .…”
Section: Introductionmentioning
confidence: 99%